2020
DOI: 10.1002/jcp.29752
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic collagen elements as signaling hubs in the regulation of tumor growth and metastasis

Abstract: Structural remodeling of the extracellular matrix is a well‐established process associated with tumor growth and metastasis. Tumor and stromal cells that compose the tumor mass function cooperatively to promote the malignant phenotype in part by physically interacting with intact and structurally altered matrix proteins. To this end, collagen represents the most abundant component of the extracellular matrix and is known to control the behavior of histologically distinct tumor types as well as a diversity of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 100 publications
(354 reference statements)
0
18
0
Order By: Relevance
“…These fragments in turn can regulate a wide array of biological processes, including angiogenesis, cell migration, adhesion and differentiation as well as tumor growth and metastasis [ 323 ]. It was found that matrikines can originate from collagen [ 324 , 325 ], elastin [ 326 , 327 ], tenascin [ 328 , 329 ], fibronectin [ 330 , 331 ], laminins [ 332 ], decorin, thrombospondin and versican [ 333 ].…”
Section: Degradation Of the Tumourigenic Matrixmentioning
confidence: 99%
“…These fragments in turn can regulate a wide array of biological processes, including angiogenesis, cell migration, adhesion and differentiation as well as tumor growth and metastasis [ 323 ]. It was found that matrikines can originate from collagen [ 324 , 325 ], elastin [ 326 , 327 ], tenascin [ 328 , 329 ], fibronectin [ 330 , 331 ], laminins [ 332 ], decorin, thrombospondin and versican [ 333 ].…”
Section: Degradation Of the Tumourigenic Matrixmentioning
confidence: 99%
“…The matricryptines are generated by the structural or enzymatic modification of ECM resulting in exposure of the biologically active and previously hidden ("cryptic") sites. It has been suggested recently that cryptic collagen elements serve as signaling hubs regulating tumor metastasis and growth (33). ECM may also evolve releasing biologically active substances, including matrikines, which may be used as "protein fingerprint" of cancer.…”
Section: Ecm Components As Cancer Biomarkersmentioning
confidence: 99%
“…The release of this sequestered VEGF regulates vascular patterning and can transform normal angiogenesis into a pathological process [ 29 ]. In addition to merely degrading the basement membrane, proteolytic cleavage of collagen type IV results in exposure of cryptic binding sites hidden in the triple helical structure that facilitates EC adhesion and migration and is required for angiogenesis in vivo [ 30 ]. Blocking these cryptic sites inhibits retinal angiogenesis in vivo [ 28 ].…”
Section: Discussionmentioning
confidence: 99%